Teaching English through Stories: A Meaningfuland Fun Way for Children of Islamic Elementary School at Widodaren Ngawi to Learn English - Nining Wulandari (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2017)
This article presents the results of a study on utilizing stories for teaching English as a foreign language to children in first, second and third grades. It was carried out in an Islamic elementary school in Widodaren Ngawi. The article was initiated by a group of student-teachers at Islamic elementary school Widodaren Ngawi. During the research process the student-teachers were required to plan the course syllabus, create their own stories according to the children's interests and likes, plan the lessons, and collect and analyze data. Although the student-teachers worked in different grade levels, the results of the study present similarities such as the children's motivation when the stories were told or read, increased participation in the different activities, comprehension of the stories, and acquisition of the new vocabulary.